The relationship between first pass recanalization of stent-retriever-based thrombectomy and neutrophil to lymphocyte ratio in middle cerebral artery occlusions. (3rd July 2021) - Şengeze, Nihat; Giray, Semih
Abstract: Background: Inflammatory response plays an important role in the process of ischemic stroke. Rapid, sustained and complete reperfusion is the most important modifiable prognostic factor for a favorable clinical outcome in patients receiving endovascular treatment (EVT). The studies related to the clot contents regarding the high level of leukocyte clots that are difficult to recanalize are quite remarkable. We aimed to investigate the relationship between Neutrophil to lymphocyte ratio and recanalization at the first pass thrombectomy. Methods: Study was conducted from February 2015 to December 2018. Patients with stroke were treated with mechanical thrombectomy. The normality of distribution of continuous variables was tested by Shapiro–Wilk test. The Mann–Whitney U test and Chi-square test was used to assess relations between variables. ROC curve analysis was performed to determine the cut-off value for NLR. Results: There were 84 patients included the study, the mean age 62.8 ± 12.9; 61.9% (52/84) that were female; median (IQR 25–75) NIHSS 16 (14–19) treated with stent-retriever-based thrombectomy. The distribution of NLR was skewed ( p value for 1-sample Kolmogorov–Smirnov test: <0.001). In terms of recanalization outcomes, the patients with NLR < 3.51 showed a significantly higher rates of successful recanalization (AUC = 0.671 ± 0.06; p  = 0.005). Conclusion: This study demonstrates that higher admission NLR values are independent predictors of unsuccessful recanalization first pass in MCA M1 occlusion of stroke patients treated with mechanical stent-retriever-based thrombectomy. Future large cohort and structural analysis of thrombi studies are needed to further explore the role of NLR as a prognostic neuroinflammatory biomarker for successful recanalization in EVT of stroke.